Diagnosing and managing delirium in the elderly. - Conn, D. K. (2001)
OBJECTIVE: To outline current approaches to diagnosing and managing delirium in the elderly. QUALITY OF EVIDENCE: A literature review was based on a MEDLINE search (1966 to 1998). Selected articles were reviewed and used as the basis for discussion of diagnosis and etiology. We planned to include all published randomized controlled trials regarding management but found only two. Consequently, we also used review articles and recent practice guidelines for delirium published by the American Psychiatric Association. MAIN FINDINGS: Clinical diagnosis of delirium can be aided by using DSM-IV criteria, the Delirium Symptom Interview, or the confusion assessment method. Management must include investigation and treatment of underlying causes and general supportive measures. Providing optimal levels of stimulation, reorienting patients, education, and supporting families are important. Pharmacologic management of delirium should be considered only for specific symptoms or behaviours, e.g., aggression, severe agitation, or psychosis. Only one randomized controlled trial of tranquilizer use for delirium in medically ill people has been published. Findings support the current belief that neuroleptics are superior to benzodiazepines in most cases of delirium. Most authorities still consider haloperidol the neuroleptic of choice. Controlled trials of the new atypical neuroleptics for treating delirium are not yet available. Benzodiazepines with relatively short half-lives, such as lorazepam, are the drugs of choice for withdrawal symptoms. CONCLUSION: Delirium is frequently underdiagnosed in clinical practice. It should be suspected with acute changes in behaviour. Careful investigation of the underlying cause permits appropriate management.